Weight-for-height and mid-upper-arm circumference should be used independently to diagnose acute malnutrition: policy implications. Issue 1 (December 2016) - Grellety, Emmanuel; Golden, Michael
Abstract Background Anthropometric surveys of children are used to assess the nutritional status of a population. World Health Organization (WHO) recommends that either mid-upper-arm circumference (MUAC) or weight-for-height Z-scores (WHZ) are used to assess acute malnutrition prevalence. However, there are reports from several countries that the two criteria identify different children. In order to examine the external validity of these observations we have compared the direction and degree of discrepancy across countries. Methods Anonymous data were collected from 1832 anthropometric surveys from 47 countries with measured children aged from 6 to 59 months and at least 75 malnourished subjects. The prevalence of total acute malnutrition and severe acute malnutrition was calculated using either absolute-MUAC or WHZ (WHO2006 standards). For each country, the total number of children diagnosed as acutely malnourished by either criterion alone or by both criteria were summed from all the surveys conducted in that country. Results In all countries a minority of children were diagnosed as malnourished by both criteria. Both the magnitude and direction of the discrepancy varied dramatically between countries with some having most children diagnosed as malnourished by MUAC and others where nearly all the children were diagnosed by WHZ alone. Eight additional countries with insufficient malnourished children were also analysed and they support the conclusions. Conclusion For all countries examined the discrepancy was not adequately explained by any single hypothesis, such as variation in relative leg to body length. The perceived need for humanitarian intervention can be affected by the measurement chosen to assess the prevalence of malnutrition which will vary from region to region. It is recommended that MUAC measurement be included in all anthropometric surveys and that the two criteria are not alternative measures of the loss of body tissue leading to an increased risk of death, but complementary variables that should both be used independently to guide admission for treatment of malnourished children.